2019
DOI: 10.1111/jep.13165
|View full text |Cite
|
Sign up to set email alerts
|

Practice of parents and pharmacists regarding antibiotics use in pediatrics: A 2017 cross‐sectional study in Lebanese community pharmacies

Abstract: Objectives:To assess practices of community pharmacists towards prescribing or dispensing antibiotics without prescription to children, determine obstacles that stand in the way of best practices, and determine whether parents misuse antibiotics when administering them to their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…Our results also showed a low prescription rate of antibiotics over the phone. Despite this promising practice, earlier studies conducted in Lebanon reported a high prevalence of inappropriate practice among community pharmacists in dispensing antibiotics without a prescription and among parents when administering them to their child (26)(27)(28). For that, we believe that educational campaigns are warranted to increase awareness on antibiotics misuse in pediatrics, and severe legislative actions should be taken to restrict such practices in order to prevent poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…In this sense, a Lebanese study identified among parents of children who used antibiotics at home that 20.6% did not follow medical instructions on the treatment dosage and duration; 64.3% terminated treatment early and diluted incorrectly. 20 According to the participants' speeches, there is a need to develop, with the relatives, guidelines with an appropriate and easy to understand language, which facilitates care continuity at home. Some participating professionals reported that practical demonstrations enable the relative to develop skills in the correct handling of the syringe and aspiration of antibiotics for solutions.…”
Section: Discussionmentioning
confidence: 99%